ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA MANAJERIAL PEGAWAI KANTOR SATUAN POLISI PAMONG PRAJA DAN WILAYATUL HISBAH KABUPATEN ACEH BESAR - Dewi Zahara (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2024)
This research was conducted at the Public Order Agency (Satpol PP) and the Regional Public Order Agency (WH) Office in Aceh Besar Regency. The aim was to examine the influence of distributive justice and procedural justice on the managerial performance of employees at the office. This research employed quantitative methods, focusing on employee managerial performance. The data source was primary data obtained through questionnaires, and multiple linear regression analysis was used for analysis. The results showed that distributive justice and procedural justice simultaneously influenced 79.4% of the managerial performance of employees at the Satpol PP and WH Office in Aceh Besar. Procedural justice tended to have a greater influence on managerial performance, accounting for 58.1%, while distributive justice had a 33.4% influence.